Analisis Kekuatan Struktur Pasca Retrofitting pada Kerusakan Struktur Balok Beton Bertulang - Luluk Kristanto; Sumargo; Muhammad Iqbal (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
The provisions exceed of crack and deflection problems, causing retrofit as best alternative methods more than the conventional. This experimental research determines damage parameters, FRP StrongGlass E450 retrofits design capacity and the behavior of reinforced concrete beams post-retrofitting. Hammer Test results for existing beams with hlap (270 mm) < hmin (286 mm), the minimum concrete quality K.408 not reflecting beam ductile behavior that exceed of allowable cracked and deflection conditions. It has not yet caused collapse, where the tensile test results with fy average 348,47 MPa and fu average 491,32 MPa still exceed the minimum strength, so the BjTP 12 installed contributes maximum for beam ductility. The similarity field deflection values with theoretical analysis and SAP 2000, made SAP 2000 modeling as FRP design, where 1 layer StrongGlass E450, 200 mm wide along 3 beams object, fulfilling flexural strength requirements, shear strength and deflection. Loading test post with sand weighing 4200 Kg (increased 25,98%) in 3 stages, the tensile strength increased 23,879% (117,325 MPa) and strain max. 0,00154 indicates the beam before yielded. Post-density injection could be affects beam stiffness on deflection, pre-retrofit P1 (-34 mm) and P2 (-37 mm), and post-retrofit P1 (-30,8 mm) and P2 (-34,2 mm).